Three new species of Ammonicera from the Eastern Pacific coast of North America, with redescriptions and comments on other species of Omalogyridae (Gastropoda, Heterobranchia) - Sartori, André F.; Bieler, Rüdiger (Zootaxa, 2014)
The family Omalogyridae comprises some of the smallest known marine snails. Like all micromolluscs, they have been historically neglected and are underrepresented in faunistic surveys. Based on a few focused studies of the family, 15 valid omalogyrid species were previously recognised in the Indian and Pacific Oceans. To these, we add 3 new species based on a morphological analysis of material in the dry collection of the Natural History Museum of Los Angeles County, applying light and scanning electron microscopies. The new species, Ammonicera mcleani, A. mexicana and A. sleursi, are the first omalogyrid species described from the Eastern Pacific coast of North America. Redescriptions of the Australian omalogyrids Ammonicera sucina (Laseron, 1954) and Omalogyra liliputia (Laseron, 1954) are also presented, detailing for the first time ultrastructural aspects of their shell morphology. Additionally, we present here the first record of Ammonicera binodosa Sleurs, 1985b in Sri Lanka, introduce the new combination Ammonicera vangoethemi (Sleurs, 1985c) for Omalogyra vangoethemi, and formally remove Transomalogyra Palazzi & Gaglini, 1979 from Omalogyridae by fixing its type species as Homalogyra densicostata Jeffreys, 1884. Finally, we present lists, geographic records and a bibliography of all currently recognised omalogyrid species in the Indian, Pacific and Antarctic Oceans, as well as an update to a previously published compilation of the Atlantic and Mediterranean representatives of the family.